ANALISIS KUALITAS PELAYANAN ADMINISTRASI KEPENDUDUKAN DI KECAMATAN KLARI KABUPATEN KARAWANG - Ahmad Kevin Maulana; Endang Larasati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
This research was compiled to find out and analyze the services quality of population administration at Klari Subdistrict Karawang Regency. This research is a descriptive qualitative research. It means researcher collected the data through interviews, observation, and literature. The data information was taken from the Secretary and staff of Klari Subdistrict In this study, researcher used the dimensions of transparency, responsiveness, assurance, empathy and direct evidence to see the Services Quality of population administration at Klari Subdistrict Karawang Regency. Based on observations and interview , the services quality of population administration at Klari Subdistrict is considered to be good enough .Based on ten indicator of five dimension: tangible , reability , responsiviness , assurance , emphaty, only some indicators are still considered low. disadvantages include , the absence of air conditioning like fan and ac, whos affecting the comfortable of community , and then lack of physical facilities like a bench around the counters and waiting room and lacking discipline of some employees .Overall public services in klari is considered to be good, although there are still some things that needs to be repaired and optimized .